Hungary - TUC leaflet, 1956 (reverse) (1956)
1956 "Hungary - TUC leaflet, 1956 (reverse)" [T0357b.jpg], 1956, Trades Union Congress Following the crushing of the Hungarian Uprising in October 1956, the TUC issued this statement condemning the action of the Soviet Union. A 'Help for Hungarian Workers Fund' was also established to send aid to Hungary and to refugee camps in Austria.